Seasonality and solar radiation variation level in benign paroxysmal positional vertigo. (3rd June 2019) - Zuma e Maia, Francisco Carlos; de Fraga, Rayane Brum; Ramos, Bernardo Faria; Cal, Renato Valério; Mangabeira Albernaz, Pedro Luiz
Abstract: Background: Several studies have shown that the incidence of benign paroxysmal positional vertigo (BPPV) presents seasonal variations and there is evidence that the variation in time is dependent on the patient's amount of vitamin D. Objectives: This is a retrospective study to verify if there is a correlation between the incidence of BPPV and the level of solar radiation, essential for the synthesis of vitamin D in the skin. Material and methods: This study comprised 214 patients with BPPV seen from 2012 to 2017, in a city Latitude: −30.0277, Longitude: −51.2287 30° 1′ 40″ South, 51° 13′ 43″ West. The amounts of monthly solar radiation were analyzed in relation to the dates of their first consultations. Statistical tests were employed to verify the existence of a correlation between solar radiation and the incidence of the disease. Results: The statistical analysis revealed a significant difference between the incidence of BPPV and the amount of radiation during the month of the diagnosis of the disease. There was also a significant statistical correlation with the climatic variation. Conclusion: More patients with benign paroxysmal positional vertigo (BPPV) are seen in consultation in the months with low solar radiation and in the autumn and winter seasons, in this geographic city.